Snow-White and the seven dwarfs. - Grimm, Jacob, 1785-1863; Grimm, Wilhelm, 1786-1859; Jarrell, Randall, 1914-1965; Burkert, Nancy Ekholm (Farrar, Straus, and Giroux, 1972)
Retells the tale of the beautiful princess whose lips were red as blood, skin was white as snow, and hair was black as ebony.